Training programmes for development workers: an overview and assessment of current status - Zainuddin, Alang Perang (1980)
Malaysia has been recognised by the international community as a nation with a fast growing economy. Her phenomenal growth is ributed to her ability to plan and mobilize her resources for the development of both the agricultural and non-agricultural sectors. These efforts among others include the opening of new agricultural land as well as rehabilitation of neglected and less productive land,provision of agricultural credit facilities,promotion of group action through specially created rural institutions,and finally the provision of better educational opportunites for her citizen.